Kim Chi-Ha's Han Anthropology and Its Challenge to Catholic Thought - Considine, Kevin P. (Horizons, 2014)
The Korean anthropology of han remains an untapped resource for envisioning Roman Catholic soteriologies within a globalizing context. Han refers to the deep wounds of the violated that are imbued with energy that will cause either creation or destruction. One means by which Catholic theologians can engage han is through the writings of Korean poet Kim Chi-Ha (b. 1941). Kim's works, Groundless Rumors: The Story of a Sound, Torture Road—1974, and Chang Il-Dam, provide evocative and challenging images of han and how God works for the salvation of both sinned-against and sinner in this world. Kim's artistic rendering of han in his works challenges Catholic soteriology to attend as thoroughly to salvation for the "sinned-against" as to salvation for sinners.